BS in the boardroom: Benevolent sexism and board chair orientations - Oliver, Abbie G.; Krause, Ryan; Busenbark, John R.; Kalm, Matias (Strategic Management Journal, 2018)
[Research summary: Though research has focused on the ascent and acceptance of female CEOs, the post-promotion circumstances female CEOs face remain unclear. In this study, we focus on a critical post-promotion circumstance: the board chair-CEO relationship. Drawing on the gender stereotype literature, agency theory, and stewardship theory, we posit that firms appointing a female CEO are more likely to adopt a collaboration board chair orientation and less likely to adopt a control orientation. We further predict this effect is attenuated by female board representation. Using a sample of new S&P 1500 CEOs, we find support for our predictions regarding the collaboration orientation but not the control orientation. This research provides some evidence of benevolent sexism in the boardroom, with female directors acting as a countervailing influence. Managerial summary: Whereas the notion that females encounter a glass ceiling on their path toward CEO is well documented, the conditions female CEOs encounter after promotion are less understood. The relationship between the board chair and the CEO is one important post-promotion condition. Board chairs can focus on monitoring and/or working together with the CEO. We suggest board chairs are more likely to work in close collaboration with female CEOs than with male CEOs. We attribute this to benevolent sexism, which explains that board chairs are more likely to collaborate with female CEOs because they view females as more conducive to, and in need of, this type of relationship. We also suggest this benevolent sexism is less prevalent when there are more females on the board.]